S.C. Consul's Probation of Offenders Act : with states rules and central and states allied legislation - Consul, S. C.; India (India : Law Book Co., 1988)
Includes text of the Probation of Offenders Act, 1958 (Act No. 20 of 1958)
Spine title: Consul's Probation of Offenders Act
Includes index
Keywords: Probation -- India